Padrões Setoriais de Inovação na Indústria Brasileira - Campos, Bruno (2009)
The article aims investigate features of the technical change in Brazilian industry. The literature related to sectoral patterns of innovation is utilized as theoretical framework, whereas hierarchical and non-hierarchical clustering analyses are used as methodological resource. Utilizing the Industrial Survey of Technological Innovation (PINTEC 2000) of the Brazilian Geography and Statistics Institute (IBGE) will be analyzed five features of the industrial technological innovation: the innovative sources, the knowledge and learning processes, the technological trajectories, the innovative outputs, and the market structure/performance. The results show that intersectoral diversity cannot be neglected to understand the innovative performance of Brazilian industry. Although some specificities, the innovative conduct of Brazilian industrial sectors are coherent with the international literature.